Perbandingan Sensor TEV Dan Detektor RC Untuk Pengukuran Partial Discharge Pada Peralatan Tegangan Tinggi - Dedi Tri Laksono; Deni Tri Laksono; Monika Faswia Fahmi; Ummul Khair; Umar Khayam (Pusat Riset dan Inovasi Nasional, 2023)
Electrical equipment often faces various issues, with insulation problems being a major cause of failure. This article investigates the comparative effectiveness of two Partial Discharge (PD) detection methods: using Transient Earth Voltage (TEV) sensors and Resistor-Capacitor (RC) detectors. The study was conducted on a metal box with a voltage level of 6 kV. Data collected included Background Noise (BGN) and Partial Discharge Inception Voltage (PDIV), processed using Microsoft Excel and OriginPro 9. Results indicate a correlation between higher BGN values on TEV sensors and earlier PDIV occurrence on those sensors. Background noise significantly impacts the PDIV threshold, influencing sensitivity and insulation risk potential. While PDIV provides a threshold guideline, correlation with BGN helps illustrate the background conditions' influence on PD measurement outcomes. The study offers insights into the importance of considering noise in PD measurements and formulates recommendations for practitioners to choose appropriate detection methods based on specific environmental conditions and electrical equipment.